Effect of phosphorus and mulching on root growth parameters, nutrient interrelations and biomass productivity of wheat (Triticum aestivum) in a mountain Alfisol - PARMAR, DEVENDER K; SHARMA, PRITAM K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at Palampur during 1990-91 and 1991-92 to study the effect of phosphorusapplication @O, 26,52, 78 kg/ha and mulches, ie no mulch, pine needles (Pinus longifolia camara), wild sage (Lantanacamara) and polyethylene sheet on root-parameters and productivity at different growth stages of wheat (Triticumaestivum L. emend. Fiori & Paol.) grown on a mountain Alfisol of Western Himalayas. The application of P up to 78kg/ha significantly and positively improved the root-weight, root-volume and root-mass density as also the productivityof wheat crop. Among the different mulching materials incorporated, the polyethylene mulch emerged superior inimproving the root growth parameter compared with the no mulch application. The root growth paramaters showed apositive and significant association with the uptake of nutrients by wheat crop.